Basal cell carcinoma of the auricle: A common lesion at an uncommon location - Ajay Pal Singh Kataria; Aravinda Konidena; Gagan Puri; Rajesh Gupta (Wolters Kluwer Medknow Publications, 2015)
Basal cell carcinoma is the most common skin cancer, accounting approximately for 70% of all skin malignancies. It develops most frequently on the exposed surfaces of the skin, middle third of the face, and the scalp. Though it is a slow-growing tumor that rarely metastasizes, it can cause significant local destruction with disfigurement if neglected or treated inadequately. We present one such interesting case of a 70-year-old female patient with a non-healing ulcer involving the left ear and the retroauricular area since 2 years. An incisional biopsy was performed from the left pinna, which was conclusive of nodular basal cell carcinoma. The clinical presentation, differential diagnosis, along with appropriate review of literature are presented in the context that dental surgeons might often be the first health care professionals to come in contact with patients suffering from abnormalities in the orofacial region.